Pengembangan Model Asesmen Formatif untuk Meningkatkan Integritas Akademik dan Kejujuran Siswa Sekolah Dasar - Lailatul Zulfa; Siti Mumun Muniroh (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to develop a formative assessment model that can improve academic integrity and honesty of elementary school students. The research method used is research and development (R&D) with the following stages: preliminary study, product development, and limited trials. Data were collected through observation, interviews, and questionnaires, and analyzed quantitatively and qualitatively. The results show that the developed formative assessment model is effective in increasing reflective awareness, academic responsibility, and honesty culture in the classroom. The implications of this study emphasize the importance of integrating character values in teachers' daily assessment practices.